Proceso de atención de enfermería en paciente con trauma abdominal penetrante por arma de fuego - Álvarez Eugenio, Alexis Ronaldo; Centeno Dávila, Steven Leonardo; Mora Veintimilla, Gladis del Rocío (My University, 2022)
The nursing care process plays an important role in the recovery of the health of the patients, promoting actions that satisfy the needs of the same person, and that in the present day one of the main causes of death is penetrating abdominal trauma caused by a firearm , often associated with multiple complications at the level of organs and systems that require invasive treatments increasing the risk of suffering infections, to avoid this, the nurse must apply a care plan aimed at improving the health of the patient and his quality of life. Objective: Apply the nursing care process to a patient with penetrating abdominal trauma by a firearm with the aim of responding to human needs by providing a better quality of care in health. Material and methods: A qualitative methodology was used, through an analytical, descriptive, observational and cross-sectional study on a patient diagnosed with penetrating abdominal trauma caused by a firearm, developing a care plan based on the theory of Marjory Gordon . Results: good education on the part of the personal nurse for the patient and his family, along with good cleaning and aseptic technique to change the ileostomy bag and drains prevents the development of undesired infections, The astringent diet reduces negative loss, During the activity and rest thanks to the techniques used, such as massages, physical rehabilitation, changes in position, skin care, muscle tone is preserved.
El proceso de atención de enfermería cumple un papel importante en la recuperación de la salud de los pacientes, fomentando acciones que satisfacen las necesidades del mismo, ya que en la actualidad una de las principales causas de muerte son el traumatismo abdominal penetrante por arma de fuego, asociándose muchas veces a múltiples complicaciones a nivel de órganos y sistemas que requieren tratamientos invasivos aumentando el riesgo de sufrir infecciones, para evitar esto el enfermero debe aplicar un plan de cuidados dirigidos a mejorar la salud del paciente y su calidad de vida. Objetivo: Aplicar el proceso de atención de enfermería en paciente con trauma abdominal penetrante por arma de fuego con el fin de responder a sus necesidades humanas proporcionando una mejor calidad de atención en salud. Material y métodos: Se utilizó una metodología cualitativa, a través de un estudio analítico, descriptivo, observacional y de corte transversal en un paciente con diagnóstico de trauma abdominal penetrante por arma de fuego, elaborando un plan de cuidados basado en la teoría de Marjory Gordon. Resultados: una buena educación por parte del personal enfermero hacia el paciente y sus familiares, junto con una buena limpieza y técnica aséptica para el cambio de bolsa de ileostomía y drenes evita el desarrollo de infecciones no deseadas, La dieta astringente disminuye la pérdida negativa, en cuanto a la actividad y reposo gracias a las técnicas empleadas como masajes, rehabilitación física, cambios de posición, cuidados de la piel se logra conservar la tonicidad muscular.
Keywords: TRAUMA ABDOMINAL; NUTRICIÓN PARENTERAL; ENFERMERIA.